1974
DOI: 10.1109/proc.1974.9462
|View full text |Cite
|
Sign up to set email alerts
|

Experimental microwave study of metal-to-metal point-contact diodes

Abstract: New characteristics obtained with metal-insulatormetal (MIM) diodes are studied. These new characteristics are interpreted according to the tunneling process, and they are compared with the characteristics one can obtain with the IN23 diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

1974
1974
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
2
5
0
2
Order By: Relevance
“…Current-voltage characteristics (CVC) of industrial diodes (GA401, GA402, DK-s7M, KD514A, D18, tunnel GI401) are typical for all such diodes. CVC of MIM diodes correspond to those described in the literature [14]- [19] [21] [22] [23].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Current-voltage characteristics (CVC) of industrial diodes (GA401, GA402, DK-s7M, KD514A, D18, tunnel GI401) are typical for all such diodes. CVC of MIM diodes correspond to those described in the literature [14]- [19] [21] [22] [23].…”
Section: Resultssupporting
confidence: 75%
“…It was found that the diodes can be divided into two groups according to the form of I sc (P) (curves 1 in Figure 6(a) and Figure 6(b), which are similar to that of MIM-diodes in ref. [19]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Les diodes. -La mesure de fréquences laser ne serait pas possible sans le dispositif non linéaire capable de produire des harmoniques et d'effectuer le mélange de plusieurs radiations optiques [4,32,33]. Ce dispositif doit posséder une bande passante de plusieurs GHz, ce qui exclut les détecteurs thermiques ou photoniques, dont la bande passante est en général inférieure à 100 MHz.…”
Section: Synthèse Des Fréquences Optiques Par Bat-unclassified
“…Интересные особенности детектирования (смена знака детектированного напряжения при росте V 0 , влияние ориентации плоскости поляризации относительно плоскости диода) наблюдались в диодах металл−изолятор−металл (МИМ) [9][10][11]. Однако нам неизвестны подобные исследования на диодах с p−n-переходом.…”
unclassified